Brustkrebs und Ernährung in der Kilimanjaro Region Tansanias : eine Fall-Kontroll Studie - Hebestreit, Antje; Justus Liebig University Giessen (My University, 2004)
Ongoing research in industrialized countries has identified links between the occurrence of malignant diseases and nutrition. An investigation of this association may be facilitated from a relatively monotonous diet of the majority of people in East Africa. As breast cancer is among the more common malignant diseases in Northern Tanzania, patients with this tumour have been selected for a case-control-study. The Kilimanjaro region in North-eastern Tanzania is chosen because of the availability of a capable partner, the Department of Histopathology of the Kilimanjaro Christian Medical Centre (KCMC). All patients suffering from primary mammary carcinoma, diagnosed at the KCMC and hospitals in the region, are included except those with HIV-infection. For each case (n=40), two individual matched controls are studied (n=80). The most important method is structured interviews about nutritional habits and lifestyle, like use of hormonal contraceptives and the reproductive habits.Expected results are information on the association between dietary intake and the occurrence of the malignancy of the mammary carcinoma. Nutritional habits are recorded by the food-frequency method witch estimates how frequently certain foods are eaten during a specific period of time (per day, week, month). In this survey, the quantitative assessment of common portion sizes are included as well. The results of the multivariate logistic regression analysis of nutrients show a positive correlation between alcohol intake and breast cancer risk (OR= 2.997; p value= 0.0205). A total fat intake of over 30% of the daily energy intake had a weak inverse effect (adjusted OR=0.618;n.s.), saturated fatty acids showed no effect (adjusted OR=0.913;n.s.). A high intake of soluble dietary fibre showed a weak protective effect (adjusted OR= 0.553;n.s.). Carotene intake showed no effect on the cancer risk (OR= 1.101;n.s.). In the multivariate model, we found - although non-significant - a higher risk associated with an early menarche (OR=1.512) and a lower risk associated with a first pregnancy at younger age (OR=0.460). The results of this case control study in Tanzania further supports the finding that alcohol consumption increases the risk of breast cancer. We found an high total fat intake associated with a lower risk. The higher fat intake of the controls may be less detrimental because of the fat quality: the study population consumes self made sunflower and maize germ oil. Plant derived fat and oils seem to decrease the risk compared to animal fats. According to our findings - no single dietary factor exerts a direct effect on the breast cancer risk except for the food quality. The higher fruit, vegetable, and legume intake of the control group led to an higher intake of fibres, vitamins and minerals. Further research is needed to identify possible associations between breast cancer incidence and nutritional factors based on a much bigger number of cases and population-based enrolment of controls.
Breast Cancer and diet in the Kilimanjaro Region of Tanzania : a Case-Control Study
Keywords: Brustkrebs; Ernährung; Lebensstil; Reproduktion; Tansania; breast cancer; diet; lifestyle; reproduction; Tanzania; ddc:610